Positive somatostatin receptor scintigraphy correlates with the presence of somatostatin receptor subtype 2. Issue 1 (January 1996) - John, M; Meyerhof, W; Richter, D; Waser, B; Schaer, J C; Scherübl, H; Boese-Landgraf, J; Neuhaus, P; Ziske, C; Mölling, K; Riecken, E O; Reubi, J C; et al.
Abstract : Somatostatin receptor scintigraphy (SRS) is positive in approximately 75% of all patients with neuroendocrine gastroenteropancreatic tumours. This study aimed to identify specific somatostatin receptor (sstr) subtypes, which are responsible for the in vivo binding of the widely used somatostatin analogue, octreotide in human neuroendocrine gastroenteropancreatic tumours. Twelve patients underwent SRS with radiolabelled octreotide. After surgical resection, tumour tissues were analysed in vitro for somatostatin and octreotide binding sites by autoradiography. In addition, for the first time, sstr subtype mRNA expression was examined by semiquantitative reverse transcription polymerase chain reaction (RT-PCR). Tumour tissues from all SRS positive patients were positive by autoradiography. Semiquantitative RT-PCR revealed most prominently sstr2 expression in scintigraphically positive tumours. Two SRS negative tumours contained in vitro octreotide binding sites as well as high levels of sstr1 and sstr2 mRNAs. Positive SRS is mainly due to sstr2. sstr1, 3, 4, and probably 5 are less important for in vivo octreotide binding. False negative scintigraphic results seem to be influenced by factors independent of the expression of specific sstr.